2013
DOI: 10.1159/000350609
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with the Use of Illicit Substances among Male University Students in Kuwait

Abstract: Objectives: To estimate the prevalence of illicit use of substances and identify the factors associated with illicit drug use among male students in the state-run Kuwait University and private universities in Kuwait. Subjects and Methods: The study was a cross-sectional survey with a sample of 1,587 male students from both private universities (n = 869) and the public (n = 718) Kuwait University in Kuwait. A self-administered questionnaire was used to collect data. Overall lifetime prevalence of substance use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
68
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 18 publications
12
68
2
7
Order By: Relevance
“…al., 2012;Hernández-Pozo et al, 2008). The result found in this study in terms of prediction differed from the result observed in the literature, which predominantly indicates that good mental health conditions predict good academic performance (Bajwa et al, 2013;Costa et al, 2012;Costales & Neira, 2011;Turner et al, 2012). As verified for social skills, the studies cited were not longitudinal like this research, which can explain the different results.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…al., 2012;Hernández-Pozo et al, 2008). The result found in this study in terms of prediction differed from the result observed in the literature, which predominantly indicates that good mental health conditions predict good academic performance (Bajwa et al, 2013;Costa et al, 2012;Costales & Neira, 2011;Turner et al, 2012). As verified for social skills, the studies cited were not longitudinal like this research, which can explain the different results.…”
Section: Discussioncontrasting
confidence: 93%
“…mental health problems like anxiety, depression and drugs use negatively affect the college students' academic performance (Bajwa et al, 2013;Castaño-Perez & Calderon-Vallejo, 2014;Costales & Neira, 2011;Hernández-Pozo et al, 2008;Turner et al, 2012), except in Costa et al (2012), who found a relation between depression indicators and good academic performance. In the analysis of these studies, it is verified that the majority found a relation between mental health indicators and academic difficulties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most affected are young people and women [19]. In the Middle East, Kuwait has reported 14% lifetime prevalence of illicit drug use [20] with Iran reporting 8% prevalence [5]. Studies in Asia noted a trend of combining illicit drug use with other substances [18].…”
Section: Substance Use Disorders Among University Students In Asiamentioning
confidence: 99%
“…In addition, drug dealers easily get couriers among the thousands of expatriate laborers entering Kuwait [6] . Another survey conducted among university students in Kuwait revealed that the total lifetime prevalence of illicit drug use was 14.4% and the most frequently used illicit substance was marijuana (11%) [7] . On multivariate logistic regression analysis, drug use was significantly associated with age, poor academic performance, high family income, being an only child in the family, divorced parents and graduation from a private high school [7] .…”
Section: Gulf Regionmentioning
confidence: 99%